College mathematics for business, economics, life sciences, and social sciences - Barnett, Raymond A.; Ziegler, Michael R. (Upper Saddle River Prentice-Hall, 1996)
Contents: a beginning library of elementary functions; additional elementary functions; mathematics of finance; systems of linear equations, matrices; linear inequalities and linear programming; probability; data description and probability distributions; markov chains,...
Keywords: Cơ bản